Inhaling the Opiumregie: Dynamics of the Opium Trade in Semarang 1901-1930: Menghisap Opiumregie: Dinamika Perdagangan Candu di Semarang 1901-1930 - Nina Witasari; Ulinnuha Auliyya Lathifa (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study examines Semarang’s role in the colonial opium trade during the transition from the pachtstelsel to the Opiumregie between 1901 and 1930. Employing a qualitative historical method using Koloniaal Verslag, Staatsblad regulations, newspaper archives, and supporting literature, the research traces the shift from private monopolies controlled by Chinese pachter to a centralized state monopoly. The findings reveal that the Opiumregie increased colonial revenue, strengthened administrative control, and reorganized distribution through government-managed depots, positioning Semarang as a principal hub in both legal and illegal opium networks. As a major port, Semarang facilitated smuggling routes that persisted despite tighter regulation. These developments had significant social impacts, particularly on port laborers who faced growing dependency, declining welfare, and rising urban problems linked to addiction and criminality. The study’s novelty lies in highlighting Semarang’s strategic yet understudied role within the opium economy of colonial Java, illustrating how state policy, maritime trade, and local social dynamics were closely intertwined.